Comparative effect of chronic administration of chloroquine phosphate and methanol extract of Landolphia owariensis on the activities of rat Enzymes - Ilesanmi F F, Balogun E A, Ilesanmi O S (Journal of Applied Pharmaceutical Science)
Medicinal plants and drugs are usually abused through wrong dose usage. These practises may pose a great health risk to the users. The objective of this work is to compare the effect of chronic administration of extract of Landolphia owariensis and Chloroquine phosphate on the activities of enzymes in the kidney, liver, and serum. The methanol extract of Landolphia owariensis and Chloroquine phosphate were administered orally to albino rats on daily doses of 250mg/kg and the activities of enzymes were monitored for 12 days. A total of 36 albino rats were divided into three. Chloroquine phosphate was administered to 12 rats, Landolphia owariensis was administered to another 12 rats and saline solution was administered to the remaining 12 as control. The results revealed that the rats administered with Landolphia owariensis showed an insignificant increase in alkaline and acid phosphatase activities in both liver and kidney. The activity of enzymes in the liver and kidney decreases significantly with chloroquine administration P< 0.05. The comparative studies of the chloroquine and Landolphia owariensis extract showed that chronic administration of chloroquine has detrimental effect on tissues, while the chronic administration of Landolphia owariensis extract causes little or no damage to the tissues.
Keywords: Landolphia owariensis, kidney, liver, serum, chloroquine phosphate, alkaline